Putting Mutual Exclusivity in Context: Speaker Race Influences Monolingual and Bilingual Infants' Word‐Learning Assumptions. Issue 5 (2nd July 2021) - Weatherhead, Drew; Kandhadai, Padmapriya; Hall, D. Geoffrey; Werker, Janet F.
Abstract : Previous work indicates mutual exclusivity in word learning in monolingual, but not bilingual toddlers. We asked whether this difference indicates distinct conceptual biases, or instead reflects best‐guess heuristic use in the absence of context. We altered word‐learning contexts by manipulating whether a familiar‐ or unfamiliar‐race speaker introduced a novel word for an object with a known category label painted in a new color. Both monolingual and bilingual infants showed mutual exclusivity for a familiar‐race speaker, and relaxed mutual exclusivity and treated the novel word as a category label for an unfamiliar‐race speaker. Thus, monolingual and bilingual infants have access to similar word‐learning heuristics, and both use nonlinguistic social context to guide their use of the most appropriate heuristic.